Insecticide Resistance And Its Underlying Mechanisms, And Product Evaluations Against Tropical Bed Bugs, Cimex Hemipterus (Fabricius) (Hemiptera: Cimicidae) - Leong, Xin Yeng (2022)
Chemical control remains as the principal mean of bed bug control in Malaysia despite insecticide resistance of bed bugs being widely documented. To date, there are fewer studies reported on insecticide resistance of C.x hemipterus as compared to C. lectularius . This study aims to investigate insecticide resistance status and its underlying mechanisms in eight field C. hemipterus strains collected in Malaysia and Australia. A C. lectularius (Monheim) susceptible strain was used as reference as no susceptible C. hemipterus strains were found. The C. hemipterus strains were evaluated for their resistance levels using commercialized residual liquid formulations, permethrin-impregnated (ActiveGuard) mattress liner, and technical grade insecticides. Insecticide classes investigated include pyrethroids (deltamethrin, lambda-cyhalothrin, beta-cyfluthrin, d-tetramethrin, cyphenothrin, d-phenothrin), neonicotinoids (thiamethoxam, imidacloprid), organophosphates (fenitrothion, chlorpyrifos), pyrrole (chlorfenapyr), and organochlorine (DDT). The parameters evaluated include developmental stages, exposure period, and mortality observation time. Results detected pyrethroid, neonicotinoid, organophosphate, and pyrrole resistance in adults of all C. hemipterus strains, exhibiting low to extremely high resistance levels. First instars demonstrated substantially lower resistance status than adults. Insecticide resistance was detected at egg stage